2006
DOI: 10.1111/j.1755-618x.2006.tb02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Town, Big Benefits: The Ripple Effect of 7/day Child Care*

Abstract: Dans cet article, l'auteure présente quelques résultats d'une enquête d'approche qualitative auprès de méres et d'éducatrices visant à analyser les répercussions du programme éducatif québécois (service de garde offrant des places pour une contribution parentale de 7 par jour) sur une ville frontière defavorisée. L'étude, qui présente un échantillon des commentaires de mères et d'éducatrices, constitue la première phase d'un projet de trois volets. l'article démontre comment un investissement dans les enfants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Parents often commute long distances to work, restricting childcare options even further and requiring parents to find care during non-standard hours or to coordinate a mixture of formal and informal care (De Marco et al, 2009;Fletcher et al, 2010). Albanese (2006) found that opening and closing hours were an important factor for mothers in a small Quebec town, who were juggling shift work and/or commuting as well as selecting a childcare centre. These mothers often needed to organise complex networks of formal and informal care to meet their families' needs, but they considered the availability of affordable childcare to be a key component of their ability to work outside the home (Albanese, 2007).…”
Section: Services For Rural Families and Childrenmentioning
confidence: 98%
See 1 more Smart Citation
“…Parents often commute long distances to work, restricting childcare options even further and requiring parents to find care during non-standard hours or to coordinate a mixture of formal and informal care (De Marco et al, 2009;Fletcher et al, 2010). Albanese (2006) found that opening and closing hours were an important factor for mothers in a small Quebec town, who were juggling shift work and/or commuting as well as selecting a childcare centre. These mothers often needed to organise complex networks of formal and informal care to meet their families' needs, but they considered the availability of affordable childcare to be a key component of their ability to work outside the home (Albanese, 2007).…”
Section: Services For Rural Families and Childrenmentioning
confidence: 98%
“…However, unlike the substantial body of literature about urban parents, few studies have explored the strengths, weaknesses, or concerns that might be unique to rural parents. Researchers have specifically explored the distribution and use of childcare in rural communities (Albanese, 2006;De Marco et al, 2009;Fletcher et al, 2010;Son and Bauer, 2010) and have demonstrated differences in the culture, demographics, and service delivery between urban and rural communities (see Martinez-Brawley, 2000 andPugh, 2007 for examples from social work; Rice andSmith, 2001 andWakerman et al, 2008 for examples from healthcare). However, little research has explored parents' experiences with early learning and care services in rural communities, or addressed whether aspects of rural life and location influence these experiences.…”
Section: Experiences Of Rural Parentsmentioning
confidence: 99%
“…A simplified family allowance was introduced to complement the federal National Child Benefit (Roy & Bernier, 2007). Quebec's income tax laws were reformed, removing parents' refundable tax credit for child care expenses (the federal one remains), when it introduced $5.00 per day (increased to $7.00 per day in 2004) child care for children using child care at least three days a week, regardless of family income and employment status (Government of Quebec, 2006;Albanese, 2006;Government of Quebec, 2003;Tougas, 2001aTougas, , 2002aTougas, , 2002bBégin, Ferland, Girard, & Gougeon, 2002). It introduced full-time, full-day kindergarten for five-year-olds and for four-year-olds living in "at-risk" neighbourhoods, and expanded school daycares at a reduced fee ($5.00 per day per child; later $7.00) for school-aged children in need of before-and after-school care (Albanese, 2011;Japel, Tremblay, & Côtè, 2005), such that by 2005 there were 1,613 daycare services in Quebec schools, resulting in 81% of public elementary schools offering them (Commission on Elementary Education, 2006;Tougas, 2001b).…”
Section: Child Care Policy In Canada and In Quebec And Ontariomentioning
confidence: 99%
“…This woman's experiences may lead some to wonder whether Quebec's generosity merely subsidizes gendered low wages (see Albanese, 2006), but the alternative in Ontario seems worse. Quebec's social policies have contributed to significant increases in women's labour force participation rates, particularly since the introduction of low fee child care (see Roy, 2006).…”
Section: More Differences -Ontario Mothers More Lucky (And Less Suppomentioning
confidence: 99%
“…Since the mid-1990s, Quebec began transforming its policies, introducing more feminist-informed programs aimed at integrating paid work and family, promoting gender equity, and reducing family poverty (Albanese 2011b;Roy & Bernier, 2007;Jenson, 2001). One of the province's major policy reforms came in 1997, when it introduced $5 per day (increased to $7.00 per day in 2004) child care for children using care at least 3 days a week, regardless of family income and employment status (Albanese 2011b;Government of Quebec, 2003Albanese, 2006;Tougas, 2001aTougas, , 2001bTougas, , 2002aTougas, , 2002bBégin, Ferland, Girard, & Gougeon, 2002).…”
Section: Child Care Policy In Canada Ontario and Quebecmentioning
confidence: 99%